Mechanical characterization of basalt woven fabric composites: numerical and experimental investigation - Piergiorgio Valentino (Frattura ed Integrità Strutturale, 2014)
Basalt fabric composite, with different twill wave reinforcements, i.e. twill 2/2 and twill 1/3, have been studied in this work by means of experimental tests and numerical finite element (FE) simulations. As fabric reinforcements show repeating undulations of warp and fill yarn, simple mixtures law cannot be applied. As a consequence, the mesoscopic scale, lying between the microscopic and the macroscopic one, has to be taken into account to mechanically characterize a fabric reinforced composite. The aim of this work is to evaluate the stiffness of a fabric reinforced composite in warp and fill direction. In particular a numerical FE model, assuming elliptical sections and sinusoidal shape of the yarns, has been implemented and experimental tests have been carried out in order to validate the proposed model. Finally, the strength and the failure modes of the composite material, for each analysed structure and textile orientation, have been experimentally investigated.